Understanding the Responses of Child Victims of Violence to Social Services: Toward Trauma-Informed Support Interventions - Murphy, Caffaro; Luthar, Luthar (Institute for Law and Economics Studies, 2022)
This research delves into the responses of children affected by violence to social services, aiming to illuminate their experiences, needs, and interactions with support systems. Utilizing a mixed-methods approach, qualitative and quantitative data were gathered from a diverse group of children who had encountered various forms of violence and engaged with social services. The findings reveal a spectrum of responses among the participants, highlighting both positive outcomes and areas requiring improvement. Positive experiences included enhanced emotional well-being and a sense of security attributed to the support received, while challenges centered on disparities in service provision, cultural insensitivity, and limited accessibility. The implications drawn from these nuanced findings call for tailored, trauma-informed, and culturally sensitive interventions that address the unique needs and responses of each child. Recommendations encompass policy reforms, practice enhancements, and service improvements, emphasizing the necessity for equitable access, trauma-informed care, cultural responsiveness, and strengthened family and community engagement. Ultimately, this research underscores the imperative of transforming findings into actionable measures, fostering a nurturing environment that prioritizes the well-being, dignity, and recovery of children affected by violence